2001
DOI: 10.1021/jp0105600
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Barite (001)− and (210)−Water Interfaces

Abstract: The structures of the barite (001) and (210) cleavage surfaces were measured in contact with deionized water at 25°C. High resolution (∼1 Å) specular X-ray reflectivity and atomic force microscopy were used to probe the step structures of the cleaved surfaces and the atomic structures of the barite-water interfaces including the structures of water near the barite-water interfaces. The barite (001) and (210) cleavage surfaces are characterized by large (>2500 Å) domains separated by unit-cell steps (7.15 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 29 publications
10
64
0
1
Order By: Relevance
“…A number of experimental and theoretical studies have been reported for the rutile (110)/water interface (Fitts et al 2005;Zhang et al 2004) and for the muscovite (001)/water interface Park and Sposito 2002;Wang et al 2005). Kerisit et al (2008) reported MD simulation results for the orthoclase (001)/water and orthoclase (010)/water interfaces that closely reproduce the experimental X-ray reflectivity data reported by Fenter et al (2003). The comparison between experimental data and simulation results was undertaken by generating an electron-density profile for adsorbed water molecules.…”
Section: Other Simulated Systemssupporting
confidence: 67%
See 2 more Smart Citations
“…A number of experimental and theoretical studies have been reported for the rutile (110)/water interface (Fitts et al 2005;Zhang et al 2004) and for the muscovite (001)/water interface Park and Sposito 2002;Wang et al 2005). Kerisit et al (2008) reported MD simulation results for the orthoclase (001)/water and orthoclase (010)/water interfaces that closely reproduce the experimental X-ray reflectivity data reported by Fenter et al (2003). The comparison between experimental data and simulation results was undertaken by generating an electron-density profile for adsorbed water molecules.…”
Section: Other Simulated Systemssupporting
confidence: 67%
“…Stack and Rustad (2007) simulated water at the (001) barite/water interface. When compared to experimental X-ray reflectivity data obtained by Fenter and co-workers Fenter and Sturchio 2004), the simulated results showed profiles that were substantially different. Among the possible reasons proposed to explain this discrepancy is the fact that simulations are conducted on a very small surface area, necessarily perfect, while experiments are conducted on large samples which certainly contain some heterogeneity because, for example, of surface reconstruction and slight deviations in the cut angle used to prepare the surface (Stack and Rustad 2007).…”
Section: Other Simulated Systemsmentioning
confidence: 76%
See 1 more Smart Citation
“…Highly ordered water structure has been observed experimentally on a wide range of minerals including calcite (CaCO 3 ) (GEISSBUHLER et al, 2004), barite (BaSO 4 ) (FENTER et al, 2001), orthoclase (KAlSi 3 O 8 ) (FENTER et al, 2003), hematite (TANWAR et al, 2007;TRAINOR et al, 2004) and alumina ( -Al 2 O 3 ) (ZHANG et al, 2008). To gain added insight into this ordered structure, computer simulations provide a complementary tool for investigating this interface.…”
Section: Introductionmentioning
confidence: 99%
“…These typically show modifi cations of the average positions of atoms in a few of the top-most monolayers of a crystal surface due to the creation of the interface. For example in the barite {001} surface, in XR experiments (Fenter et al 2001) and MD simulations (Stack and Rustad 2007), show a bulk-like structure after about three monolayers depth, which is about 1 nanometer (Fenter et al 2001) (Fig. 6).…”
Section: Substrate and Precipitate Effectsmentioning
confidence: 99%